Production of free surface water jets using focused underwater shock waves - Karnovsky, Hilton (My University, 2014)
It is possible to produce concentrated free surface water jets by rapidly accelerating a geometrically shaped curved deflector plate below the free water surface. This principle has been established using a self focusing electromagnetic acoustic source (FEMAS) and this report verifies it using a shock tube based mechanical analogue of that system. The shape, form and speed o f the water jets produced vary between the two systems. Discrete pressure measurements using a needle hydrophone positioned at different points below the free water surface are presented. The variation in pressure amplitudes recorded highlight the scatter and uncertainty inherent in a complex coupled system, while the form o f the pressure trace is dependant on the mechanical design o f the system in use and the position o f the needle hydrophone in the pressure field. To better understand the experimental system, a computer simulation using commercially availa ble non-linear dynamic analysis software has been developed. This shows that the water surface jets result from the overall hydrodynamic, flow initiated by rapid movement o f the deflector plate below the water surface.